A global network of scholars? The geographical concentration of institutes in migration studies and its implications - Piccoli, Lorenzo; Ruedin, Didier; Geddes, Andrew (Comparative migration studies, 2023)
The study of international migration and responses to it has experienced rapid growth in the last three decades: an institutionalisation of migration studies. This paper identifies and specifies infrastructural and semantic elements of institutionalisation by establishing a global Directory of Migration Research Institutions identifying 282 institutes focused on migration research that were operative between 1945 and 2020. We observe a clear geographical concentration in the Americas and Europe and find that most institutes are in countries with higher economic development (GDP) and net immigration (not emigration). Using this evidence, we suggest that the institutionalisation of migration studies is driven by concerns and ideas produced in high-income ‘destination’ countries. We thus show that uneven knowledge production in migration studies is not only caused by exclusive categories, language, or journal policies, but also by a structural problem at an earlier stage: because of fewer resources invested in the creation of institutionalised academic knowledge structures, lower income countries have fewer possibilities to shape the semantic features of the field of migration studies, by which we mean the identification of subjects of interest, concepts, narratives, and priorities.